Cardiac magnetic field map topology quantified by Kullback–Leibler entropy identifies patients with clinically suspected myocarditis - Pille, M.; Gapelyuk, A.; Berg, K.; Bannasch, S.; Mockler, J.; Park, L.-S.; Park, J.-W.; Wessel, N. (Frontiers in Cardiovascular Medicine, 2023)
Background: Myocarditis is a condition that can have severe negative outcomes and lead to sudden cardiac death if remaining undetected. In this study, the capability of cardiac magnetic field mapping to detect patients with clinically suspected myocarditis is tested. This could open up the way for rapid noninvasive and cost-effective screening of suspected cases prior to a gold standard assessment via endomyocardial biopsy. Methods: Historical cardiac magnetic field maps (n=97) and data from a state-of-the-art magnetocardiography device (n=30) were analyzed by means of the Kullback-Leibler Entropy (KLE) for dimensionality reduction and topological quantification. Linear discriminant analysis was used to discern between patients with ongoing myocarditis and healthy controls.Results: The STT segment of a magnetocardiogram, i.e. the section between the end of the S wave and the end of the T wave, is best suited to discern both groups. Using a 250 ms excerpt from the onset of the STT segment gave a reliable classification between the myocarditis and control group for both historic data (Sensitivity: 0.83, Specificity: 0.85, Accuracy: 0.84) and recent data (Sensitivity: 0.69, Specificity: 0.88, Accuracy: 0.80) using the KLE to quantify the topology of the cardiac magnetic field map.The implementation based on KLE is able to reliably distinguish between clinically suspected myocarditis patients and healthy controls. We implemented an automatized feature selection based on LDA to replace the observer-dependent manual thresholding in previous studies.